Low Back Pain Among Students of Medical University of Tunis - Boussaid, Soumaya; Daldoul, Cyrine; Rekik, Sonia; Jammali, Samia; Cheour, Elhem; Sahli, Hela; Elleuch, Mohamed (Current Rheumatology Reviews, 2023)
Objective: Low Back Pain (LBP) is the most common musculoskeletal disorder among working adults. It is one of the most prevalent complaints among students. Medical students are among those who are most exposed to this condition; due to stress, numerous hours of studying, and the sedentary lifestyle. Our study aimed to determine the prevalence and associated factors of LBP among the students of Tunis Faculty of Medicine and to assess its impact on student life. Methods: This cross-sectional study was carried out on the Tunis Faculty of Medicine students. Data were collected through an online self-administered questionnaire. Sociodemographic, personal, and lifestyle characteristics were collected. LBP was assessed using the Nordic Musculoskeletal Health Questionnaire and Its impact using the Oswestry Disability Index (ODI). Results: One hundred and forty-eight students were included. The mean age was 22.9 ± 2.3 years (19.64-38.21). The sex ratio was 0.29. According to the Nordic questionnaire, the point, annual and lifetime prevalence of LBP were 37.8%, 80.4%, and 90.5%, respectively. The mean ODI score was 10.32 ± 8.48 % (0-32). The ODI score was minimal in 87.3% and moderated in 12.7% of cases. The associated factors with LBP were: young age (p = 0.015), spending more than 4 hours in a sitting position (p = 0.059), second cycle of medical studies (p = 0.006), low screen projection in the amphitheater (p = 0.029) and poor layout of the amphitheatres (p = 0.000). The feeling of depression was significantly higher among LBP students (p = 0.018). In the multivariate analysis, the factors that remained statistically significant were the second cycle of medical studies (OR= 3.41), feeling of depression (OR = 3.7), and the belief in the responsibility for the poor layout of the amphitheaters in the genesis or maintenance of LBP (OR = 7.66). Conclusion: LBP in medical students is multifactorial across both personal and college-life domains.
Keywords: Low back pain